Strengthening National Identity To Younger Generation Through Internalization Of Pancasila Values In The Digital Era - Fadhilah, Nur; Triyanto,; Rukayah, (International Journal of Psychosocial Rehabilitation, 2020)
The existency of digital era has spread in all generation, especially the younger generation which is the next generation of the nation. National identity as the important part of a nation needs to be firmly embedded to the younger generation. The basic of national identity of Indonesia is Pancasila (five basic principles). This study aims to explain the process of strengthening the national identity to the younger generation through internalization of Pancasila values in the digital era and analyze the obstacles found during the process. The research subject was the youth club of Sidomulyo Village. The results of the study indicate that the process of strengthening the national identity to the younger generation is carried out through pro-social activities such as regular monthly meetings and blood donation events. Some of the obstacles encountered in the process are the differences of thinking and the difficult permit process. This research is expected to provide information and foundation in determining activities to strengthen the national identity of the younger generation in the digital era.